Impact of the Culture of the Organization, the Working Environment Contacted with Laboral Stress and the Variable of Intervening in the Wide of Vocational Training and Productivity - Listiyorini, Ety; Kasmir, Kasmir (Indonesian Journal of Business Analytics, 2023)
The aim of this research is to find the influence of organizational culture, work environment on job satisfaction with work stress as a mediation variable. The primary data was obtained from the results of the questionnaire to 116 respondents using the probability sampling technique. (SEM-PLS). The results of the study found Organizational culture has a significant negative influence on employee work stress, Working environment has a negative and significant influence upon employee job stress, Organizational cultures have a positive and significant impact on employees job satisfaction, The work environment has an important and positive impact on the employee’s work satisfaction, Working stress has a positive influence and significant effect on employees’ work satisfactions, The organizational culture influences employee satisfaction through work stress mediation, The working environment influences employees’ satisfaction with the mediation of work stress in the main room vocation training and productivity.